Media Coverage of Covid-19 and Readers’ Perception of Credibility of Fake News - Joshua Kayode Okunade (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2025)
Fake news is not new, nevertheless, new communication technologies have allowed for new ways to produce, distribute, and consume fake news which makes it harder to differentiate what information to trust and it is especially evident in this period of COVID-19. This study investigates the online media coverage of COVID-19 and Readers’ Perceptions of source credibility of fake news. The objectives of the study are: to find out the level of infiltration of COVID-19 fake news vide the Nigerian online news space and to ascertain how this has affected the credibility of Nigerian online Newspapers by its readers. The study employed the Source Credibility theory, and the Theory of Rumor Transmission. The study method was a survey method with an administration of four hundred copies of the questionnaire. 383 questionnaires were collected and found useable for analysis, representing 96.14% of the administered instrument, and ideal enough for the generalization of the study’s findings to a large population. This study therefore recommended that journalists should strictly adhere to the essentials of news reportage and dissemination which are accuracy and truthfulness to maintain quality in the media while paying paramount attention to media and information literacy and new fact-checking services.